Analisis Multivariate Adaptive Regression Splines (MARS) pada Prediksi Ketertinggalan Kabupaten Tahun 2014 - Siskarossa Ika Oktora (Jurnal Aplikasi Statistika & Komputasi Statistik, 2015)
The purposes of this research are to build underdeveloped regency model and make a prediction in 2014 based on economic categories, Human Resources (HR), infrastructures, fiscal capacity, accessibility, and regional characteristics with MARS method. MARS is a classification method which can handle highdimensional data with unknown pattern in advance, and can be applied to see the interaction between variables. MARS is an alternative method when the data doesn’t fulfil the parametric statistics assumptions. From MARS model, there are three variables that affect underdeveloped regency, they are consumption expenditure per capita, life expectancy, and percentage of household electricity users. The accuracy of MARS model is very high, 97.83 percent and can be used to make a prediction. Based on MARS model, at the end of the National Development Plan 2010-2014 is predicted a significant transitions in regency’s status. This model can also be used to predict the condition of new regency based on empirical data, because in the earlier classification, the status of regency just follows the status of parent region.